Cell culture processes for biopharmaceutical manufacturing - Gadgil, Mugdha (Current Science, 2017)
Recombinant proteins manufactured using animal cell culture processes comprise a significant fraction of biopharmaceuticals. With the expiry of patents on this class of therapeutics, there is also a significant interest in manufacture of biosimilar versions of such therapeutics. This article provides a birds-eye view of upstream process development for animal cell culture processes, with a focus on advances pertinent to the development of processes for biosimilars.
Keywords: Biopharmaceutical; Cell line development; CHO; glycosylation; monoclonal antibody